PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN WISATA ALAM RIAM PANGAR DI DESA PISAK KECAMATAN TUJUH BELAS KABUPATEN BENGKAYANG - Iskandar A M; Sofyan Zainal; Emelisa Sely; Marwanto Marwanto (Universitas Tanjungpura, 2023)
Bengkayang Regency is a district with abundant natural tourism potential, one of which is Riam Pangar, located in Pisak Village, Tujuh Belas District. Riam Pangar's development aims to support nature conservation by opening a tourism area. It is necessary to know the public perception of the development of natural tourism in Riam pangar. It needs to be studied more deeply so that these negative impacts can be overcome and the community can participate in its development. The relationship of individual factors of knowledge, income, and cosmopolitanism with people's perceptions of the development of natural tourism Riam Pangar. This research uses a survey method with a purposive sampling technique. The results showed that the community's perception of the development of Riam Pangar nature tourism in Pisak village, Tujuh Belas sub-district tended to be positive, with a percentage of 58.89%, there was a significant relationship between the level of community knowledge on the development of Riam Pangar nature tourism. Keywords: Development, Riam Pangar nature tourism, Community Perception